PENERAPAN PENDEKATAN INQUIRI DAPAT MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SDN 014 BASILAM BARU - Darbi, Ahmad Darbi Ahmad; Alpusari, Mahmud Alpusari Mahmud; ', Munjiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract. The problem is research in this study is the result of third-grade students learn science SDN 014 Basilam Baru still low or insufficient KKM set by the school at 65, which reaches only 11 people KKM 47.28% for the classically expected learning research with the application of the inquiry approach to the formulation of the problem "if the application of this approach can improve the results of the inquiry science at third grade students of SDN 014Â  BasilamÂ  Baru". The hypothesis of this study is to apply this approach when applied to the inquiry it will improve learning outcomes IPA third grade students of SDN 014 Basilam Baru. This research is a form of class research (PTK). The subjects were 014 students in grade III SDN 014 Basilam Baru second half of 2013 to 2014 the number of students the teaching of as many as 23 people. Consisted of 12 male students and 11 female students. The data collected from the observation. Keywords: application of the inquiry approach, SAIN learning outcomes